La política de innovación en Colombia - Montenegro, Iván (2017)
The purpose of the article is to support the main role of an effective public policy of innovation, science and technology, oriented to contribute to productive development and social inclusion. To this objective, a strong conceptual framework is adopted that emerges from the threefold failure: market, system and State. It supports policy´s key components such as: governance and focus on science, innovation, and productive development. There is awareness that in the world there exists a set of methods, models and techniques that facilitate the achievement of seemingly contradictory objectives. Among the challenges presented, note is made of the support of science, innovation, and productive development to post-conflict Colombian nation and territory and to the economy´s informal sector.